2021
DOI: 10.1002/cam4.4038
|View full text |Cite
|
Sign up to set email alerts
|

Worse capecitabine treatment outcome in patients with a low skeletal muscle mass is not explained by altered pharmacokinetics

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“… 29 The previously identified increased toxicity and decreased survival in patients with low SMM could therefore not be explained by changes in pharmacokinetic characteristics of capecitabine and its metabolites. 29 In addition, according to a pharmacokinetic study, in 184 oesophageal cancer patients treated with paclitaxel, skeletal muscle measures were not superior to BSA in predicting pharmacokinetics of paclitaxel and did not have any added value to BSA. 30 …”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“… 29 The previously identified increased toxicity and decreased survival in patients with low SMM could therefore not be explained by changes in pharmacokinetic characteristics of capecitabine and its metabolites. 29 In addition, according to a pharmacokinetic study, in 184 oesophageal cancer patients treated with paclitaxel, skeletal muscle measures were not superior to BSA in predicting pharmacokinetics of paclitaxel and did not have any added value to BSA. 30 …”
Section: Discussionmentioning
confidence: 94%
“…In addition, patients with low SMM were generally more likely to receive a lower cumulative cisplatin and carboplatin dose compared with patients with intermediate or high SMM, which is a potential validation of the need for dose reduction or different treatment regimens in patients with low SMM compared with patients with intermediate/high SMM. In a recent study among 151 patients with solid tumours treated with capecitabine (a hydrophilic chemotherapeutic agent), no alterations in pharmacokinetics of capecitabine and the active and toxic metabolite 5‐FU were observed in patients with low SMM 29 . The previously identified increased toxicity and decreased survival in patients with low SMM could therefore not be explained by changes in pharmacokinetic characteristics of capecitabine and its metabolites 29 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Nevertheless, no changes in the PK properties of CAP and 5-FU were observed in patients with a low SMM. Therefore, the previously identified increased toxicity and shorter survival in patients with a low SMM, could not be explained by alterations in PK characteristics of CAP and its metabolites [ 33 ]. Taken together, substantial evidence indicated that systemic exposure to CAP and its metabolites in plasma was poorly predictive of safety and efficacy, which seemed to defeat the value of therapeutic drug monitoring for dosage adjustment [ 15 ].…”
Section: Discussionmentioning
confidence: 99%